Prevalence of Puumala virus (PUUV) in bank voles (Myodes glareolus) after a major boreal forest fire - Nematollahi Mahani, Seyed Alireza (2016)
Our knowledge on the impact of forest fires on the prevalence (proportion of infected individuals in a population) and dynamics of zoonotic pathogens is largely limited. A large forest fire in late 2006 at Bodträskfors in northern Sweden provided a unique opportunity to investigate the effect of habitat change on disease prevalence. Pummala virus (PUUV) is one of the most prominent zoonotic viruses in this northern boreal forests with bank vole as its only competent host. Human’s infection occurs by breathing the aerosolized viral particles shed through saliva, urine and feces of the infected host. The infection causes Nephropathia Epidemia, a milder form of hemorrhagic fever with renal syndrome. The disease has relatively low death rates but can cause lifelong symptoms in humans. Here I have investigated the prevalence of PUUV in bank voles between spring and autumn of 2007-2010 and again in 2015. Small mammals were trapped in trapping plots in the Bodträskfors forest fire area (n=7), mature reference forests (n=7) and unburned clear-cuts (3).